IMPLEMENTATION OF PANCASILA VALUES IN SUPPRESSING THE RADICALISM MOVEMENT - Febrian Nanda Putra Sukarna; Subelo Wiyono (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Pancasila, as a state ideology, encourages unity, tolerance and diversity in society. The Indonesian government has played an important role in promoting and maintaining Pancasila values ​​as a tool to prevent radicalization. This includes education, laws, regulations and outreach that support these values. Society also plays a key role in maintaining Pancasila as the foundation of unity and stability. Despite success in many aspects, challenges in suppressing radicalism movements remain and require continued efforts. Awareness of Pancasila values ​​and commitment to them is key in ensuring that Indonesia remains a peaceful and diverse country.